Beispiel Nr: 15
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +2 y =-4\\ -1 x +2 y = 5 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +2 y =-4\\ II \qquad -1 x +2 y = 5 \\ \text{I nach y auflösen}\\ 1 x +2 y =-4 \\ 1 x +2 y =-4 \qquad /-1 x\\ 2 y =-4 -1 x \qquad /:2 \\ y =-2 -\frac{1}{2} x \\ \text{II nach y auflösen}\\ -1 x +2 y =5 \\ -1 x +2 y =5 \qquad /+1 x\\ 2 y =5 +1 x \qquad /:2 \\ y =2\frac{1}{2} +\frac{1}{2} x \\ \text{I = II}\\ -2 -\frac{1}{2} x =2\frac{1}{2} +\frac{1}{2} x \qquad /+\frac{1}{2} x /-2\frac{1}{2} \\ -2-2\frac{1}{2} =\frac{1}{2} x +\frac{1}{2} x \\ -4\frac{1}{2} =1 x \qquad /:1 \\ x=-4\frac{1}{2} \\ \text{x in I}\\ y =-2 -\frac{1}{2} \cdot -4\frac{1}{2} \\ y=\frac{1}{4} \\ L=\{-4\frac{1}{2}/\frac{1}{4}\} \end{array} & \begin{array}{l} I \qquad 1 x +2 y =-4\\ II \qquad -1 x +2 y = 5 \\ \text{I nach x auflösen}\\ 1 x +2 y =-4 \\ 1 x +2 y =-4 \qquad /-2 y\\ 1 x =-4 -2 y \qquad /:1 \\ x =-4 -2 y \\ \text{II nach x auflösen}\\ -1 x +2 y =5 \\ -1 x +2 y =5 \qquad /-2 y\\ -1 x =5 -2 y \qquad /:\left(-1\right) \\ x =-5 +2 y \\ \text{I = II}\\ -4 -2 y =-5 +2 y \qquad /+2 y /+5 \\ -4+5 =2 y +2 y \\ 1 =4 y \qquad /:4 \\ y=\frac{1}{4} \\ \text{y in I}\\ x =-4 -2 \cdot \frac{1}{4} \\ x=-4\frac{1}{2} \\ L=\{-4\frac{1}{2}/\frac{1}{4}\} \end{array} \end{array} $